Pengembangan Packed Flow Reactor Tipe Fixed Bed untuk Meningkatkan Efisiensi Metanasi CO₂ Menggunakan Katalis Nikel - Apriyansah, Apriyansah; Yerizam, Muhammad; Hasan, Abu (Innovative: Journal Of Social Science Research, 2024)
The increase in carbon dioxide (CO₂) emissions due to human activities poses a significant challenge to climate change. CO₂ methanation, the process of converting CO₂ into methane (CH₄), offers a potential solution for reducing carbon footprints and producing useful fuel. This study focuses on developing a fixed bed packed flow reactor made of stainless steel, with a capacity of ±2 liters, to enhance CO₂ methanation efficiency. Nickel (Ni) catalysts were selected due to their relatively low cost and good performance. Experiments were conducted at temperatures up to 400°C to optimize CH₄ production. The results show that higher temperatures increase methane production, with an optimal temperature of 100°C resulting in 39.41% CH₄. Lower CO₂ flow rates also increase CH₄ production due to longer contact times. Higher temperatures reduce residual CO₂, and the amount of active sites on the catalyst affects the reduction of residual CO₂.